(untitled) (Medico Legal Update, 2020)
Diabetic retinopathy (DR) is a retinal disease which is one of the most severe micro vascular complications occurring due to diabetes mellitus and is a major cause of blindness. The aim of this work was to study the serum level of omentin-1 and its relation to diabetic retinopathy in type 2 diabetes mellitus. The study included 60 diabetic patients (30 patients T2DM complicated with DR and 30 patients T2DM not complicated with DR). The study also included 30 healthy control individuals defended as subjects who apparently haven’t any chronic diseases. Thorough history taking and physical examination with calculation of body mass index (BMI), investigations were done including HbA1c, C-reactive protein (CRP) and serum omentin-1. Fundus examination was carried out by an expert ophthalmologist. The study showed that serum omintin-1 was reduced significantly (P<0.001) in DM patients (15.29±3.69 ng/ml) as compared with the control group (24.95±4.22 ng/ml), Table 1. The study also showed that serum omintin-1 was reduced significantly (P<0.001) in DR patients (12.39±2.21 ng/ml), comparing with DM patients without retinopathy (17.52±2.28 ng/ml). The study revealed that the highest mean of HbA1c was found in DM patients (8.39±1.62 %) as compared by the control group (4.91±0.43 %) (P<0.001), Table 3. The study also found that HbA1c was elevated significantly (P<0.001) in DR patients (9.38±1.65 %) comparing with DM patients without retinopathy (7.66±0.79 %) (P<0.001). The study showed that, the highest mean of serum CRP was recorded in DM patients (7.89±1.76 mg/dl), as compared with the control group (4.51±0.72 mg/ dl) (P<0.001), Table 5. The study also found that CRP was elevated significantly (P<0.001) in DR patients (9.37±1.11 mg/dl) as compared with diabetic without retinopathy patients (6.41±0.73 mg/dl), The study showed that 60% DR patients suffered from T2D for more than 9 years and 40% suffered DM for 7-9 years while all diabetic patients without retinopathy were suffered from T2D for ? 9 years with a significant relation between Dr and the duration of diabetes (P<0.001). The study showed negative correlation of serum omentin-1 concentrations with duration of diabetes, BMI, HbA1c and CRP. From this study we can conclude that serum omentin-1 levels are correlated with the presence and severity of DR.